L’exposition de la performance, entre reenactment et tableau vivant : les cas de Marina Abramovic ainsi que d’Alexandra Pirici et Manuel Pelmus - Boucher, Mélanie (Muséologies, 2015)
Expositions that consist of presentation of performances have an interest in generating a series of questions on the types of performances that are favourable for occupying space and time. What are they? This article retraces two types, re-enactment and the tableau vivant, and presents their main characteristics. These types of performances are prone to induce modifications in exhibition practices, and through that, raise questions regarding the relationship between research and creation. The cases, Seven Easy Pieces (2005), by Marina Abramovic at the Solomon R. Guggenheim, and An Immaterial Retrospective of the Venice Biennale (2013), by Alexandra Pirici and Manuel Pelmus at the Venice Biennale, serve initially as exemplification, then as epistemic presentation of the two types of performances considered. Through strategies however comparable, Seven Easy Pieces and An Immaterial Retrospective of the Venice Biennale presume diverse purposes. The first work would have as objective, iconization, by relying on the presence of the artist, as well as on the rigour of the document research. The second work offers an example of the critical use of the exposition, by exploiting a research that is not neither put forth nor supported.